1997
DOI: 10.1002/(sici)1098-1063(1997)7:1<88::aid-hipo9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ inhibits synaptic transmission and long-term potentiation in rat hippocampus

Abstract: It is known that opioid peptides acting on opioid receptors can modulate hippocampal synaptic functions. Although a novel member of the opioid receptor family, ORL1 receptors, that displays high‐sequence homology with classical opioid receptors is abundant in the hippocampus, little is known regarding its role in synaptic function. The present study was designed to investigate whether activation of the ORL1 receptor by its natural ligand, orphanin FQ, could modulate synaptic transmission and synaptic plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 40 publications
2
31
2
Order By: Relevance
“…Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionmentioning
confidence: 65%
“…Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionmentioning
confidence: 65%
“…Furthermore, nociceptin was reported to function as an inhibitory modulator for synaptic function in the hippocampus. 6 Accordingly, we examined the effects of nociceptin on the NMDA receptor function and signal transduction through NMDA receptor. NMDA receptor is a ligand and voltage-gated Ca 2 þ channel.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 This peptide is capable of inhibiting Ca 2 þ currents through voltage-gated Ca 2 þ channels in dissociated hippocampal neurons, 4 inducing hyperpolarizing currents via inward-rectifier K þ channels in the hippocampal CA3 cells 5 or suppressing synaptic transmission in the hippocampal CA1 slices. 6 Owing to its structural similarity to classical opioids (68% homology with m receptor, 67% with d receptor, 66% with k receptor) and high density of ORL 1 receptors in the hippocampus, 7 it is of interest to explore whether nociceptin, like other opioids, modulates the synaptic plasticity and memory function in the hippocampus. Recent studies demonstrated that intrahippocampal 8,9 and intracerebroventricular 10,11 injections of nociceptin impair learning and memory in the water maze and passive avoidance tests, respectively.…”
mentioning
confidence: 99%
“…Importantly, OFQ/N has been shown to block LTP in hippocampal slices (Yu et al 1997) and impair spatial learning (Sandin et al 1997;Redrobe et al 2000) in rats. Furthermore, OFQ/N administration blocks morphine-induced conditioned place preference Ciccocioppo et al 2000) and tolerance (Lutfy et al 2001b), both of which rely on associative learning processes.…”
Section: Discussionmentioning
confidence: 99%